Influence of stirring speed on glucose and ethanol production in simultaneous saccharification and fermentation process - Palniandy, T.; Nafsun, Aainaa Izyan; Mohd Jamil, Norazaliza; Herz, F.; Azmi, N.A.A; Muhammad Zaki, M. H. (Universiti Malaysia Pahang, 2022)
Lignocellulosic biomass has a potential to be coverted to bioethanol which can be a new alternative for fossil fuel. Empty fruit bunches (EFB) is one of the most abundant lignocellulosic biomass in Malaysia, which has high content of cellulose and posses favorable physiochemical characteristics for bioethanol production via a process called simultaneous saccharification and fermentation (SSF). In SSF process, the reaction is initiated by diffusion and consolidation of the enzyme and its substrate. Thus, optimum stirring speed is crucial, as diffusion rate of substrates is influenced by the agitation of reaction mixture. The influence of stirring speed on the glucose and ethanol concentration in SSF process was investigated in the current study. Initially, 5 % (g/ml) of pretreated EFB in 1.5 liter of 0.05 M buffer citrate pH 4.8 were sterilized in autoclave at 121°C for 20 minutes. Then, enzyme Cellic Ctec-2 solution with concentration (1%) were added together with 1.5% (g/ml) Saccharomyces cerevisiae yeast in the bioreactor. The process was conducted in the bioreactor under temperature of 37°C with stirring speed of 100 rpm for 72 hours. SSF process experiments were repeated with the same setup except by varying the stirring speed (150 and 200 rpm) independently. From the results, the glucose concentration and ethanol yield of 200 rpm indicated less concentration in every 24 hours compared to 150 rpm and 100 rpm. The stirring speed of 150 rpm shows the highest glucose concentration (1.914 mg/ml) and ethanol yield (16%) obtained after 72 hours and determined as the best stirring speed for this experiment.